Exploring the driving mechanism and path of BIM for green buildings - Yang, Yuntao; Zhao, Bin; Liu, Qingli (Journal of Civil Engineering and Management, 2024)
Despite green building and BIM technology being hot spots in the construction industry, most research remains at the technical level. Leading to exploring the fundamental driving reason and mechanism of BIM for green buildings is still lacking. This paper explored BIM’s impact mechanism and driving path on green buildings from the management’s perspective to fill this gap. Based on a literature review, 18 expert interviews, and three case studies of green buildings, the influence mechanism was analysed via a qualitative method (ISM). Then, the importance of driving factors was evaluated via quantitative analysis (ANP). Specifically, this study probed the driving path by combining qualitative and quantitative analysis (ISM-ANP). The research findings show that the driving force of BIM for green buildings comes from the fundamental factor layer and is transferred to the intermediate and direct factors layer. The critical driving path of BIM for green building is to promote the visualization of building information, collaborative management, and expand real estate investment through the guidance of policies and standards. Based on research results, this paper puts forward five suggestions: 1) Improving the policy and standard system; 2) Striving to research native software; 3) Adopting an informatization project management mode; 4) Accelerating the construction and improvement of the green building industry chain; 5) Promoting government enterprise cooperation. These results may benefit not only the coupling and coordination of the two but also the construction industry’s green transformation and high-quality development.